Estimation of the economic opportunity cost of labour: An operational guide for Ghana - Glenn P. Jenkins; Richard Sogah; Abdallah Othman; Mikhail Miklyaev; Çagay Coskuner (Queen's University, Department of Economics, 2023)
The implementation of projects often affects employment through direct job creation, indirectly stimulating employment, or increasing labour force participation. These changes in employment have significant benefits and costs to both labour and society. However, the estimation of job creation benefits is challenging because of the large diversities in labour inputs. We attempt to address this issue by using the supply price approach to develop an analytical framework based on sound microeconomic principles to assist project analysts to arrive at justifiable empirical estimates of the economic opportunity cost of labour for a wide range of labour types across a set of diverse situations and market conditions in Ghana. Accordingly, the economic opportunity cost of labour will vary by skill, location, and labour market conditions that need to be incorporated into its estimation. In this analysis, the estimation has been carried out to quantify the economic opportunity cost of labour, as well as the labour externalities corresponding to the two broad categories of labour: skilled and unskilled. Similarly, these estimates refer to groups of labour according to areas of residence: rural and urban.
Keywords: O2; D61; Q42; Q48; 330; renewable energy subsidy; distributed energy resources; feed-in tariff; stakeholder analysis; benefit-cost analysis; Ontario; Canada